Do cavies talk? The effect of anthropomorphic picture books on children's knowledge about animals - Ganea, Patricia A.; Canfield, Caitlin F.; Simons-Ghafari, Kadria; Chou, Tommy (Frontiers in Psychology, 2014)
Many books for young children present animals in fantastical and unrealistic ways, as wearing clothes, talking and engaging in human-like activities. This research examined whether anthropomorphism in children’s books affects children’s learning and conceptions of animals, by specifically assessing the impact of depictions (a bird wearing clothes and reading a book) and language (bird described as talking and as having human intentions). In Study 1, 3-, 4-, and 5-year-old children saw picture books featuring realistic drawings of a novel animal. Half of the children also heard factual, realistic language, while the other half heard anthropomorphized language. In Study 2, we replicated the first study using anthropomorphic illustrations of real animals. The results show that the language used to describe animals in books has an effect on children’s tendency to attribute human-like traits to animals, and that anthropomorphic storybooks affect younger children’s learning of novel facts about animals. These results indicate that anthropomorphized animals in books may not only lead to less learning but also influence children’s conceptual knowledge of animals.